Thinking difference: Theories and models of parametric design thinking. (September 2017) - Oxman, Rivka
Abstract : The paper examines the uniqueness of seminal parametric design concepts, and their impact on models of parametric design thinking (PDT). The continuity and change within the evolution of design thinking is explored through review of key texts and theoretical concepts from early cognitive models up to current models of parametric design thinking. It is proposed that the seminal role for parametric schema, as a strategic medium of parametric design thinking, is formulated at the intersection of three bodies of knowledge: cognitive models of typological and topological design in architecture; process models of digital design; and tectonic order of material fabrication design (MFD). Differentiation is introduced as a key design strategy of PDT and is demonstrated through classification of prominent case studies. Highlights: Parametric design thinking (PDT) presents a new horizon for research and practice in design studies. PDT incorporates disciplinary knowledge, including process models and tectonic content. Outlines the evolution of design thinking from cognitive origins to PDT. Postulates and defines the role of parametric schema as a strategic medium for PDT. Identifies differentiation as a key strategy of PDT.